Teddy Roosevelt, Our Nature President - Goldish, Meish (Zaner-Bloser, Inc.)
This book is a biography of Teddy Roosevelt America's great nature president. He saw many great sights in the U.S. He loved the mountains, the forests, the lakes, and the animals. He loved nature, just as he had as a young boy. Americans will always think of Teddy Roosevelt as their Nature President.
Keywords: Juvenile Non-Fiction / Biographies